TEMUAN KISTA DENTIGEROUS PADA IMPAKSI GIGI INSISIVUS SENTRAL RAHANG ATAS PADA RADIOGRAF PANORAMIK - Azzahra, Nabila; Suparno, Nilasary Rochmanita; Haris, Mahfuzi El (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2024)
Introduction: The impacted tooth is a condition indicated by the tooth's failure to erupt into the jaw arch within the normal-expected time range. An impacted tooth is a probable cause for the dentigerous cyst. A dentigerous cyst is a fluid-filled sac of connective tissue, bordered by stratified squamous epithelium that forms around the crown of an unerupted tooth or denticle. This case report aims to define the radiography of an impacted maxillary central incisor accompanied by a dentigerous cyst via panoramic examination. Case and Management: A 22-year-old female was appointed to Soelastri Dental and Oral Hospital with complaints of ungrown teeth in the maxillary region of the mouth and discomfort during eating. There was no history of any systemic disease available nor the history of allergies. Panoramic Radiography Examination indicated an impacted tooth via the displayed radiolucency image of a dentigerous cyst lesion on the crown within the region of maxillary central incisors. Conclusion: A Dentigerous Cyst is formed due to fluid accumulation between the epithelium and the crown of an unerupted tooth. Proper panoramic radiography is imperative for an accurate diagnosis and efficient treatment planning.